The Impact of Gus Iqdam's Online Media on Religious Understanding and Participation in Sambidoplang Village - Muhammad Fikri ‘Ainun Najib; MIFTAKHUL ROHMAN (Sultan Journal of Social Sciences and Humanities, 2026)
Advancements in information and communication technology have brought about fundamental changes in how religious teachings are disseminated within society. This transformation is marked by a shift in religious outreach practices from conventional settings to the digital realm a space that is more open, flexible, and interactive. Social media platforms like YouTube and TikTok no longer serve merely as sources of entertainment; they have become strategic mediums for conveying religious messages widely and effectively. In this context, the emergence of preachers who successfully leverage digital media represents a phenomenon worthy of scholarly examination. This study aims to analyze the influence of the online media utilized by Gus Iqdam on the religious understanding and participation of the community in Sambidoplang Village. A qualitative approach was employed, utilizing a case study design and a phenomenological perspective to gain deep insight into the religious experiences of the congregation. Data were collected through in-depth interviews, participant observation, and documentation, and subsequently analyzed using the Miles and Huberman interactive model. The findings indicate that Gus Iqdam’s online media presence significantly enhances the community's religious understanding, particularly regarding practical aspects such as acts of worship and social ethics. His communicative, contextual, and humorous preaching style facilitates the internalization of religious values. Furthermore, an affective impact was observed, manifested as increased inner peace and a stronger emotional connection to religious teachings. Digital media also contributes to heightened religious participation, evident in both attendance at religious study gatherings and social interactions among congregants. These findings confirm that online media does not replace conventional religious practices; rather, it reinforces religious engagement and social cohesion within the community in the digital era.